An Early Paleozoic Inter‐Platform Shelf in the Southwest of Tarim Basin, NW China and its Significance for Petroleum Exploration. Issue 4 (October 2014) - Zhiqian, Gao; Tailiang, Fan
Abstract An early Paleozoic inter‐platform, platform, slope and shelf succession comprised of five Cambrian to mid‐Ordovician seismic sequences, has been identified in the southwestern part of the Tarim Basin. A previously unknown, elongate shelf succession that extends from east to west transects the Taxinan area of the southwestern Tarim Basin. It was flanked by carbonate platforms and platform margins, and by peri‐platform margin slopes on its north and south sides. The Markit platform margin and slope, located along the northern side of the shelf, extended nearly linearly west to east with some headlands and embayments towards the east. The Tangnan platform margin and slope, located along the southern side of the shelf, extended southwest to northeast and was more sinuous with pronounced northwest‐directed headlands flanked by embayments. Differentiation of these settings began in earliest Cambrian time during continental breakup. Initially, broad gentle slopes flanked an open shelf seaway in Cambrian time. In Early Ordovician time, the Markit and Tangnan platform margins became more distinct and rimmed, and were flanked by slightly steeper, but still very gentle slopes. During their deposition, these platform margins and their adjoining slopes exhibited some lateral migration, with a slight overall widening of the open shelf seaway between them from Cambrian to Ordovician time. The presence of these platform margin and slope successions in the southwestern area of the Tarim basin provides another focus for petroleum exploration and discovery of additional carbonate reef‐shoal reservoirs in the Markit and Tangnan areas. The adjoining deep‐water shelf shale and mudstone shelf succession itself is an additional prospective petroleum source rock in close proximity to these potential reef‐shoal reservoirs.